2002
DOI: 10.2169/internalmedicine.41.7
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Human Growth Hormone Secretion and Its Disorders.

Abstract: Growth hormone (GH) secretion from anterior pituitary is regulated by the hypothalamus and the mediators of GH actions. Major regulatory factors include GHreleasing hormone (GHRH), somatostatin (SRIF), GHreleasing peptide (ghrerin) and insulin-like growth factor (IGF-I). The principal physiological regulation mechanisms of GHsecretion are neural endogenousrhythm, sleep, stress, exercise, and nutritional and metabolic signals. GHdeficiency results from various hereditary or acquired causes, which may be isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 53 publications
1
43
0
6
Order By: Relevance
“…Acidophile-derived hormones include GH and PRL. GH synthesis and secretion is tightly regulated by a number of feedback systems; several reviews [32][33][34] expound upon specific control mechanisms of endocrine GH synthesis and regulation. In short, neurons from the hypothalamus project to the pituitary where GH releasing hormone (GHRH) secretion stimulates GH gene expression and GH secretion while somatostatin (SRIF) secretion from another subset of hypothalamic neurons inhibits GH release.…”
Section: The Pituitary and Hypothalamusmentioning
confidence: 99%
“…Acidophile-derived hormones include GH and PRL. GH synthesis and secretion is tightly regulated by a number of feedback systems; several reviews [32][33][34] expound upon specific control mechanisms of endocrine GH synthesis and regulation. In short, neurons from the hypothalamus project to the pituitary where GH releasing hormone (GHRH) secretion stimulates GH gene expression and GH secretion while somatostatin (SRIF) secretion from another subset of hypothalamic neurons inhibits GH release.…”
Section: The Pituitary and Hypothalamusmentioning
confidence: 99%
“…Like all other variants, the 22 kDa-GH is produced, by proteolytic cleavage of the somatotropin precursor under the regulation by the growth hormone releasing hormone (GHRH), somatostatin, and ghrelin [17,18]. A 22 kDa-GH deficiency in humans results in dwarfism, while excess is associated with the syndrome of acromegaly [19][20][21].…”
Section: Somatotropinmentioning
confidence: 99%
“…In corroboration, clinical studies have shown that newborns have an exaggerated response to GHRH and a delayed and blunted response to somatostatin (Delitala et al 1978, Shimano et al 1985. Postnatally, these elevated hGH levels would cause high serum levels of IGF-I and IGFBP-3, resulting in gigantism in a prepubertal child and acromegaly in an adult (Kato et al 2002). However, in the fetus, serum IGF-I and IGFBP-3 levels are very low or undetectable until late in the third trimester (Butler & Le Roith 2001, Gohlke et al 2004.…”
Section: Discussionmentioning
confidence: 93%
“…This is likely due to the greater sensitivity of the human fetal pituitary somatotrope to its hypothalamic stimulatory factor, GHreleasing hormone (GHRH), than its inhibitory factor, somatostatin, throughout in utero development (Delitala et al 1978, Goodyer et al 1993a. Similar hGH levels postnatally cause highly elevated serum levels of insulin-like growth factor-I (IGF-I) and IGF-binding protein-3 (IGFBP-3), resulting in gigantism in the prepubertal child and acromegaly in the adult (Kato et al 2002). However, circulating levels of IGF-I and IGFBP-3 in the fetus are low, reaching significant levels only late in the third trimester (Butler & Le Roith 2001, Gohlke et al 2004, suggesting a blunted responsiveness of fetal tissues to hGH during earlier stages in development, at either the hGH receptor or the signaling level.…”
Section: Introductionmentioning
confidence: 99%